Pelayanan Butler Hotel : Kreasi Nilai Melampaui Harapan Tamu di SBN Resort - Wulantari, Putu; Indrayani, I Gusti Ayu Putu Wita; Arthini, Ni Nyoman Suci (Journal of Hospitality Accommodation Management (JHAM), 2024)
Value creation as part of a holistic marketing framework is the ability of marketers to provide benefits to customers. Value creation aims to produce or make a service so needed and attractive in the eyes of consumers. Butlers have the potential to create value creation, because a butler is more be close to guests so that value creation will be easier to implement. This type of research is descriptive qualitative with an emphasis on data and information collected from interviews and documentation. The conclusion of research on value exploration services, a butler is able to understand guest preferences so that the butler can prepare guest needs according to guest expectations. In value creation, the butler creates value creation after understanding the guest's preferences, for example guests having birthdays, wedding anniversaries, honeymoons so that it can be added value in creating value creations to exceed guest expectations. In conveying value, the butler conveys the value that has been created to the guest in an effective and efficient way, for example when guests have a birthday / wedding anniversary / honeymoon prepared before the guest arrives, prepares a guest room with decorations so that the guest feels very satisfied.